Molecular-cytogenetic analysis of triticale and wheat lines with introgressions of the tribe Triticeae species genetic material - O. A. Orlovskaya; I. N. Leonova; I. G. Adonina; E. A. Salina; L. V. Khotyleva; V. K. Shumny (Вавиловский журнал генетики и селекции)
There are a number of problems in selection of cultivated cereals associated with the requirements to create forms with resistance to diseases, pests and unfavorable environmental conditions. The genetic diversity of genes for resistance to biotic and abiotic stresses can be increased by means of the gene pool of wild and cultivated wheat relatives. To improve agronomic traits in cereals, we have developed common wheat hybrid lines T. aestivum/ T. durum, T. aestivum/ T. dicoccoides and triticale lines by crossing hexaploid triticale with common wheat forms with the substitution of genome D for the genome of diploid Aegilops species. The aim of the study was to identify the lines of common wheat and hexaploid triticale with alien introgression using cytological and molecular-genetic analyses and evaluation of their cytological stability. Comparative analysis of the structure of chromosomes by GISH and FISH methods, microsatellite- and chromosome-specific markers revealed that hybridization of triticale with genome-substitution forms of wheat leads to the reorganization of the genome, including both the introgression of foreign material and wheat chromosome rearrangements, which lead to new combinations of genetic loci. The efficiency of wheat microsatellite markers to characterize of the T. aestivum/ T. durum, T. aestivum/ T. dicoccum interspecific hybrid lines was shown. From 4 to 12 translocations of different lengths from T. durum and T. dicoccum were identified in the chromosomes of A and В genomes in the hybrid lines. Meiotic stability of wheat and triticale hybrids was found. It creates prerequisites for preservation of alien genetic material in subsequent generations.